PENGARUH FORMAL COMPETENCE, AUDIT FEE, AUDIT FIRM SIZE DAN FINANCIAL DISTRESS TERHADAP OPINI GOING CONCERN - Nabella Aprilia Suma; Dul Mu'id (Diponegoro Journal of Accounting, 2019)
This study aims to examine the relationship between formal competence, audit fee, audit firm size and financial distress to going concern opinion. The sample used in this study is a non financial companies listed on the Indonesia Stock Exchange in 2017. The sampling technique are uses purposive sampling method, as many 168 companies that have met the predetermined sample criteria. This study uses logistic regression to examine hypothesis. The result indicate that formal competence, audit firm and financial distress size not have significant effect to going concern opinion. On other hand audit fee have significant effect to going concern opinion.